An unusual case of ectopic tungiasis with pseudoepitheliomatous hyperplasia - Heukelbach,J. (2004)
Tungiasis is caused by the penetration of the female sand flea Tunga penetrans into the epidermis, and subsequent hypertrophy of the parasite. In most cases lesions are confined to the feet. During a cross-sectional study, an unusual case of ectopic tungiasis in the inguinal area was detected. Histological examination of tissue samples showed a remarkable pseudoepitheliomatous aspect of the epidermis. Clinical features and differential diagnoses are discussed.